SAT0001 Antibody Response to Pneumococcal and Influenza Vaccination in Patients With RA Receiving Subcutaneous Abatacept. (23rd January 2014) - Alten, R.; Bingham, C. O.; Cohen, S.; Calabrese, L.; Curtis, J. R.; Block, A.; Fay, J.; Kelly, S.; Luo, A.; Wong, D.; Genovese, M. C.
Abstract : Background: Previous small studies have suggested that responses to some immunizations may be attenuated by intravenous abatacept but remain clinically meaningful. 1, 2 We investigated the magnitude of response to pneumococcal and influenza vaccination in a larger number of patients (pts) receiving subcutaneous (SC) abatacept therapy. Objectives: To evaluate the antibody response to the standard 23-valent pneumococcal polysaccharide vaccine and the 2011–2012 seasonal influenza trivalent vaccine in adult pts with RA on SC abatacept and background DMARDs. Methods: These multicentre, open-label sub-studies of the 23-valent pneumococcal polysaccharide vaccine and seasonal influenza vaccine enrolled pts in the ACQUIRE (pneumococcal and influenza) or ATTUNE (pneumococcal) studies. Pts were enrolled at any point during their SC abatacept treatment cycle after completion of ≥3 months' abatacept treatment. All pts received fixed-dose SC abatacept 125 mg/week with background DMARDs. A pre-vaccination blood sample was collected and vaccines administered, while continuing background SC abatacept and DMARDS. After 28 ± 3 days, a final post-vaccination blood sample was collected. For pneumococcal vaccination, the primary endpoint was the proportion of pts achieving a ≥2-fold increase in post-vaccination titres to ≥3 of 5 evaluated pneumococcal antigens (9V, 14, 18C, 19F and 23F) in the vaccine at Day 28 in pts without a protective antibody level to these antigens at baseline. For influenza vaccination, the primary endpoint was the proportion of pts achieving a ≥4-fold increase in post-vaccination titres to ≥2 of 3 evaluated 2011–2012 influenza antigens (H1N1, H3N2 and Brisbane) at Day 28 in pts without a protective antibody level to these antigens at baseline. Safety and tolerability were assessed throughout the studies. Results: Pre- and post-vaccination titres were available for 113/125 and 186/191 enrolled pts receiving the pneumococcal and influenza vaccines, respectively. Among vaccinated pts, 47/113 pneumococcal and 121/186 influenza pts were without protective antibody levels at baseline. Of these pts, 73.9% (34/46) and 61.3% (73/119) met the primary endpoint and demonstrated an immunological response to the pneumococcal vaccine or influenza vaccine, respectively. In all pts who received the vaccine and had pre- and post-vaccination antibody titres available 4 weeks post-vaccination, 83.9% (94/112) in the pneumococcal study demonstrated protective antibody levels (titre ≥1.6 μg/mL to ≥3 of 5 pneumococcal antigens), and 82.1% (151/184) in the influenza study demonstrated protective antibody levels (titre ≥1:40 to ≥2 of 3 influenza antigens). Vaccination during SC abatacept administration was well tolerated, with no new safety signals identified. Conclusions: In this group of pts with RA on SC abatacept and background DMARDS, a majority without protective antibody levels at baseline were able to mount an immune response to the pneumococcal and influenza virus vaccines, and vaccination was well tolerated. These data are consistent with previous smaller studies. References: Tay L, et al. Arthritis Res Ther 2007;9 :R38; Schiff M, et al. Arthritis Rheum 2007;56 :S392 Disclosure of Interest: R. Alten Grant/research support from: Bristol-Myers Squibb, Merck Pharma GmbH, Wyeth Pharmaceuticals, Pfizer, Consultant for: Abbott Laboratories, Horizon Pharma, Merck Pharma GmbH, Nitec Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, Speakers bureau: Abbott Laboratories, Bristol-Myers Squibb, Horizon Pharma, Merck Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, C. Bingham 3rd Grant/research support from: Bristol-Myers Squibb, Genentech/Roche, UCB, Janssen/J&J, Consultant for: Abbott, Amgen, Genentech/Roche, Janssen/J&J, Lilly, Novartis, Pfizer, UCB, S. Cohen Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, L. Calabrese Consultant for: Bristol-Myers Squibb, Centocor, Genentech/Roche, Pfizer, sanofi aventis, Savent, Antares, Speakers bureau: Amgen, Bristol-Myers Squibb, Genentech/Roche, J. Curtis Grant/research support from: Roche/Genentech, UCB, Centocor, CORRONA, Amgen, Pfizer, Bristol-Myers Squibb, Crescendo, Abbott, Consultant for: Roche/Genentech, UCB, Centocor, CORRONA, Amgen, Pfizer, Bristol-Myers Squibb, Crescendo, Abbott, A. Block Employee of: Bristol-Myers Squibb, J. Fay Employee of: Bristol-Myers Squibb, S. Kelly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, A. Luo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, D. Wong Employee of: Bristol-Myers Squibb, M. Genovese Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb